Bargaining With Charitable Promises: True Preferences and Strategic Behavior - Andreas Lange; Claudia Schwirplies (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We report experimental findings on the role of charitable promises in bargaining settings. We vary the enforceability of such promises within variants of ultimatum games where the proposer suggest a split between himself, the responder and a char-itable donation. By reneging on initial pledges, dishonest proposers can turn the bargaining power to their advantage. Providing ex post information on actual dona-tions while leaving the contract incomplete outperforms a complete contract where proposers cannot renege on their charitable promises. The ex post information allows proposers to improve their (self-)image by voluntarily giving more than pledged and thus proving that the charitable pledge was not used for strategic reasons. We identify proposer competition as another (surprising) mechanism that partly eliminates cheat-ing among accepted offers. We relate our findings to calls for information provision on actual CSR activities within the management literature.
Keywords: C90; D64; H41; L31; 330; bundling; charity; public good; donation pledges; cheating; prosocial ultimatum game; experiment